DOI: 10.11606/t.25.2015.tde-03062015-092934
|View full text |Cite
|
Sign up to set email alerts
|

Função de língua e funções orofaciais em indivíduos com disfunção temporomandibular

Abstract: A Deus, pela vida, pela saúde, por todas as bênçãos concedidas, por guiar os meus caminhos e me proporcionar oportunidades as quais nunca imaginaria alcançar. A Ele minha eterna gratidão. Ao amor da minha vida, meu esposo Enéias, pelo amor, carinho, companheirismo e incansável compreensão e incentivo. Amo muito você. À família Rodrigues e agora também Rosa, pelo apoio, incentivo e carinho. Se consegui chegar a esta etapa da vida foi graças a seus esforços. À minha orientadora, Profa. Dra. Giédre Berretin-Felix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
(162 reference statements)
0
1
1
1
Order By: Relevance
“…The averages of the present research, were lower than those found in Rosa's 17 work, whose average values of tongue pressure in patients with temporomandibular disorders (TMD) were 56.33 kPa and 58.20 kPa in the control group. This decrease in tongue pressure can be explained by changes in bone structure of the jaw and / or mandible 18 , characteristic in patients with DFD, which generate adjustments in the myofunctional stomatognathic system, which may cause lingual hypotonia.…”
Section: Discussioncontrasting
confidence: 86%
“…The averages of the present research, were lower than those found in Rosa's 17 work, whose average values of tongue pressure in patients with temporomandibular disorders (TMD) were 56.33 kPa and 58.20 kPa in the control group. This decrease in tongue pressure can be explained by changes in bone structure of the jaw and / or mandible 18 , characteristic in patients with DFD, which generate adjustments in the myofunctional stomatognathic system, which may cause lingual hypotonia.…”
Section: Discussioncontrasting
confidence: 86%
“…The values found for Con dence Ellipse and Phase were also higher than reported for healthy individuals, 18,20,22 respectively indicating greater variability in the patterns of contraction of masticatory muscles and incoordination of this musculature. The values of Mean module, Chewing symmetry and Working and balance were lower than those of healthy individuals, 18,20,22,34 showing less activity on the working side and asymmetry of muscle pattern, since 0%…”
Section: Discussionmentioning
confidence: 81%
“…Ao comparar os resultados obtidos com a literatura, pode ser observado que os valores da frequência mastigatória estão semelhantes ao estudo de Dellavia et al (2007) (FERRARIO et al, 2004;FELICIO et al, 2012 FERRARIO et al, 2004;FELÍCIO et al, 2013;FERREIRA et al, 2014), indicando, respectivamente, maior variabilidade nos padrões de contração da musculatura mastigatória e incoordenação desta musculatura. Já os valores do Módulo Médio, da Simetria Mastigatória e do Trabalho e Balanceio estiveram menores que os de indivíduos saudáveis (FERRARIO et al, 2004;FELÍCIO et al, 2013;FERREIRA et al, 2014;ROSA, 2014), demonstrando menor atividade do lado de trabalho e assimetria do padrão muscular, uma vez que 0% indica padrão assimétrico e 100% padrão simétrico. Ao comparar os valores do Trabalho e Balanceio entre os músculos, o masseter apresentou maior atividade do lado de trabalho do que o temporal.…”
Section: Função Mastigatória E Saúde Oralunclassified